DEMOCRATIC LEADERSHIP OF FEMALE SCHOOL HEADS IN THE BAREBBO DISTRICT OF BONE REGENCY - Andi Tenri Abeng; Nuraisah; Andi Ratu Ayuashari Anwar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of democratic leadership practiced by female principals at the elementary school level in Barebbo District, Bone Regency. The research employed a qualitative approach with a descriptive method. The research subjects consisted of five female principals selected through purposive sampling based on school accreditation and a minimum of five years of leadership experience. Data were collected through in-depth interviews, observation, and documentation, with analysis conducted through data reduction, display, and conclusion drawing. The findings indicate that female principals implement democratic leadership through open communication, involvement of teachers in decision-making processes, and the application of deliberation in school management. Democratic leadership is also reflected in teacher empowerment and task delegation based on individual competencies. Within the context of a strong patron–client culture in Bone Regency, female principals are able to adapt democratic leadership practices without diminishing their authority by positioning themselves as respected figures who remain open to dialogue. The implementation of this leadership style has a positive impact on creating a harmonious, collaborative, and conducive school climate, while increasing teacher motivation and sense of belonging. This study provides empirical insights into how female leadership can overcome gender stereotypes through effective participatory practices in local cultural contexts.